Somatic control over the germline stem cell lineage during Drosophila spermatogenesis. - Tran, J.; Brenner, T.J.; DiNardo, S. (Nature, 2000)
Stem cells divide both to produce new stem cells and to generate daughter cells that can differentiate. The underlying mechanisms are not well understood, but conceptually are of two kinds. Intrinsic mechanisms may control the unequal partitioning of determinants leading to asymmetric cell divisions that yield one stem cell and one differentiated daughter cell. Alternatively, extrinsic mechanisms, involving stromal cell signals, could cause daughter cells that remain in their proper niche to stay stem cells, whereas daughter cells that leave this niche differentiate. Here we use Drosophila spermatogenesis as a model stem cell system to show that there are excess stem cells and gonialblasts in testes that are deficient for Raf activity. In addition, the germline stem cell population remains active for a longer fraction of lifespan than in wild type. Finally, raf is required in somatic cells that surround germ cells. We conclude that a cell-extrinsic mechanism regulates germline stem cell behaviour.